Tertiarius minutulus sp. nov. (Stephanodiscaceae, Bacillariophyta) – a new fossil diatom species from Lake Ohrid - Zaova, Dušica; Cvetkoska, Aleksandra; Mitic-Kopanja, Danijela; Jovanovska, Elena; Ognjanova-Rumenova, Nadja; Levkov, Zlatko (European Journal of Taxonomy, 2020)
A new fossil diatom species, Tertiarius minutulus sp. nov., is described from a sediment sequence DEEP-5045-1 of Lake Ohrid. The species is characterized by small valves (3.0–8.0 µm) with a round shape, a marginal area with radially arranged costae and a central uneven area with scattered areolae. Externally, the alveoli are occluded by cribra perforated by irregularly arranged pores. Internally, the alveoli are simple and areolae are occluded with domed cribra. The marginal fultoportulae are situated on costae close to the valve margin, located on every 5th or 7th thick internal costa. One to three fultoportulae are present on the valve face, each surrounded by two to three satellite pores. One rimoportula is present, positioned on a costa at the valve face / mantle junction. The species is compared with morphologically similar taxa and a detailed differential diagnosis is provided. Tertiarius minutulus sp. nov. is known only as a fossil taxon from Lake Ohrid, with a first occurrence during the early stages of lake basin development.